2021
DOI: 10.1038/s41419-021-04320-4
|View full text |Cite
|
Sign up to set email alerts
|

The distinct responsiveness of cytokeratin 19-positive hepatocellular carcinoma to regorafenib

Abstract: Cytokeratin 19-positive (CK19+) hepatocellular carcinoma (HCC) is an aggressive subtype characterized by early recurrence and chemotherapy tolerance. However, there is no specific therapeutic option for CK19+ HCC. The correlation between tumor recurrence and expression status of CK19 were studied in 206 patients undergoing liver transplantation for HCC. CK19−/+ HCC cells were isolated to screen effective antitumor drugs. The therapeutic effects of regorafenib were evaluated in patient-derived xenograft (PDX) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Therefore, the developed 3D‐HepG2 coculture model may be useful for investigating the role of CK19 in tumor and finding new target molecules against CK19‐positive HCC. [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the developed 3D‐HepG2 coculture model may be useful for investigating the role of CK19 in tumor and finding new target molecules against CK19‐positive HCC. [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the developed 3D-HepG2 coculture model may be useful for investigating the role of CK19 in tumor and finding new target molecules against CK19-positive HCC. [44] ALB was used to investigate the liver function of all developed spheroid models. [17,23,45] To examine the liver function at different stages of spheroid growth, the supernatants were collected from day 5 (early-stage spheroids) to day 14 (late-stage spheroids).…”
Section: Protein Expression Of Liver-specific Biomarkersmentioning
confidence: 99%
“…sinensis not only serves as an independent risk factor for OS and RFS but also elevates the expression of HCC CSC markers, namely, CK19 and EpCAM. CK19+ HCC is an aggressive subtype characterized by its propensity for early recurrence, metastasis and chemotherapy tolerance as well as poor prognosis [ 45 48 ]. Oriana Miltiadous et al reported an independent association between CK19 and HCC recurrence, with a hazard ratio of 2.95 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…After RFA treatment, liver cancer recurrence increased in patients. With respect to the recurrence of liver cancer, time is used as a dividing line in many studies (Shinkawa et al 2021;Zhuo et al 2021), and recurrence is divided into early and late recurrence. In this study, early recurrence was defined as within 24 mo after ablation.…”
Section: Discussionmentioning
confidence: 99%